Effects of Lycopene and Red Palm Oil on Oxidative Stress in Streptozotocin-Induced Diabetic Rats - Jafari, Hanieh (2010)
The purpose of the current study was to determine lycopene and red palm oil effects on oxidative stress in streptozotocin-induced diabetic rats. The studied parameters for oxidative stress are fasting blood glucose level, oxidative stress biomarkers (superoxide dismutase and glutathion peroxidase), lipid profiles (low-density lipoprotein cholesterol, triglycerides, total cholesterol and high-density lipoprotein cholesterol) and body weight. For induction of diabetesFor induction of diabetesFor induction of diabetesFor induction of diabetesFor induction of diabetesFor induction of diabetesFor induction of diabetesFor induction of diabetes, the, the rats were injected with 55 mg/kg body weight of STZ (Streptozotocin) dissolved in 0.05 M citrate buffer (pH4.5). Lycopene (10 and 20 mg/kg bw) and red palm oil (10 and 20 mg/kg bw) were given to the diabetic rats by force feeding fo six weeks supplementation. The results indicated that there was significant difference in fasting blood glucose level after 6 weeks of lycopene (10 and 20 mg/kg bw) and red palm oil (10 and 20 mg/kg bw) administration as compared to diabetic control group. The supplementation with red palm oil (10 and 20 mg/kg bw) significantly (p < 0.05) reduced the plasma low-density lipoprotein cholesterol, triglycerides and total cholesterol of diabetic rats as compared to control diabetic (un-treated and super olein oil) animals. The administration with red palm oil 10 and 20 mg/kg bw, has increased the level of HDL-C in treated groups as compared to control diabetic rats. However, there were no significant changes in lipid profiles (low-density lipoprotein cholesterol, triglycerides, total cholesterol and high-density lipoprotein cholesterol) level in diabetic treated groups with lycopene (10 and 20 mg/kg bw) after six weeks supplementation. Superoxide dismutase and glutathion peroxidase activities were enhanced in diabetic treated groups with lycopene (10 and 20 mg/kg bw) and red palm oil (10 and 20 mg/kg bw) compared to that in control diabetic rats. The supplementation of lycopene (10 and 20 mg/kg bw) and red palm oil (10 and 20 mg/kg bw) significantly prevented body weight loss starting from 3rd week of lycopene and red palm oil administration in treated animals. These findings suggest that lycopene may have considerable therapeutic potential as an antioxidant but there was no significant lipid lowering effect in Type 2 diabetes mellitus. These results also showed that red palm oil (RPO) lowered the blood glucose level and improved dyslipidemia. Level of oxidative stress markers were also reduced with administration of RPO. These findings indicate antidiabetic capability of red palm oil.